Political Dynamics Of Islamic Education In Indonesia: A Systematic Review (2004–2024) - Wahyudin, Aji; Abidin, Munirul; Raharjo, Mudjia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Various literature often appears discussions about the politics of Islamic education in Indonesia, but they are rarely used as a theoretical basis because this phenomenon is dynamic. This study aims to Identify the study of the political area of Islamic education, we focus on the trend of the study span of years (2004-2024). To achieve the objectives of this study, we used a type of SLR methodology with a qualitative approach. First, we formulated a research question by focusing on two RQs, then we searched the literature through